Mặn hóa và kiềm hóa tầng đất mặt nuôi tôm ở huyện Cái Nước (Cà Mau) - Thọ, Nguyễn; Hùng, Nguyễn Thanh (Vietnam Journal of Earth Sciences, 2007)
Salinisation and sodification of the topsoils of the shrimp ponds in Cai Nuoc district, Ca Mau province